Social anchor effects in decision-making under ambiguity - Amrei M. Lahno (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
I experimentally examine whether feedback about others' choices provides an anchor for decision-making under ambiguity. In a between-subjects design I vary whether subjects learn choices made individually by a "peer" in a first part when facing the same task a second time, and whether prospects are defined over gains or losses. My key findings are that the relative ambiguity attitude (compared to the peer's) significantly matters for shifts in individual attitudes, and that dynamics considerably differ between gain and loss domains. For gains, learning to be comparably ambiguity averse increases the likelihood for such shifts, relative to the individual condition; for losses, this likelihood decreases only if peers learn to exhibit exactly the same attitude. Further, I observe imitative shifts towards the peer's attitude in the gain domain, but only towards neutrality in the loss domain. Shifts towards neutrality for losses also appear significant without social anchor suggesting that ambiguity seeking might not be particularly robust. Moreover, cognitive ability positively correlates to shifts towards neutrality in the gain domain, but has no impact in the loss domain.
urn:nbn:de:bvb:19-epub-20960-6
Keywords: C91; D03; D81; D83; 330; Decision-making under uncertainty; ambiguity; social comparison; learning; laboratory experiment.